Analysis of Potential in the Development of Tangkahan Ecotourism, Langkat Regency, Sumatra - Lubis, Juanda; Yota Balad; Mulyadi; Alexander Syam (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
This study evaluates the internal and external aspects of the Tangkahan destination in order to develop a development scheme that harmonizes economic aspects with tropical forest conservation. Using a qualitative descriptive approach, data was collected through direct observation in the field, documentation studies, and in-depth interviews with relevant stakeholders. The findings of the research through a SWOT analysis revealed that Tangkahan has a strong internal foundation with a score of 1.85, which is driven by the unique appeal of the Sumatran elephant as its main icon. However, the progress of this area is still constrained by severely damaged road infrastructure and limited telecommunication connections. From the external side, the great interest of foreign tourists in conservation activities is the main opportunity (score 0.80), but the sustainability of the ecosystem is threatened by the expansion of oil palm plantations which have an equally large threat score. The results of the IFAS and EFAS matrix mapping placed Tangkahan's strategic position at the coordinates (1.05; 0.00), which is between the aggressive and diversified strategy zones